2020
DOI: 10.3847/1538-4357/ab85cd
|View full text |Cite
|
Sign up to set email alerts
|

Three Lyα Emitting Galaxies within a Quasar Proximity Zone at z ∼ 5.8

Abstract: Quasar proximity zones at > z 5.5 correspond to overdense and overionized environments. Galaxies found inside proximity zones can therefore display features that would otherwise be masked by absorption in the intergalactic medium. We demonstrate the utility of this quasar-galaxy synergy by reporting the discovery of the first three "proximate Lyα emitters" (LAEs) within the proximity zone of quasar J0836+0054at z=5.795 (Aerith A, B, and C). Aerith A, located behind the quasar with an impact parameter =  D … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 189 publications
(204 reference statements)
6
59
0
Order By: Relevance
“…However, to date, this method has yielded only weak constraints on t Q ∼10 6 -10 9 yr owing to uncertainties in how quasars populate dark matter halos (Shen et al 2009;White et al 2012;Conroy & White 2013;Cen & Safarzadeh 2015). Following the "Soltan" argument (Soltan 1982), which states that the luminosity function of quasars as a function of redshift reflects the gas accretion history of local remnant black holes, Yu & Tremaine (2002) estimated the mean lifetime of luminous quasars from local early-type galaxies to be t Q ∼10 7 -10 8 yr. Further constraints on quasar activity on timescales between ∼10 5 and 10 7 yr have been set by measuring an ionization "echo" of the quasar, which denotes the time lag between changes in the quasar's ionization rate and the corresponding changes in the opacity of the surrounding intergalactic medium (IGM; Adelberger 2004;Hennawi et al 2006;Schmidt et al 2017;Bosman et al 2020). A recent compilation of studies on the timescales governing the growth of SMBHs can be found in Inayoshi et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, this method has yielded only weak constraints on t Q ∼10 6 -10 9 yr owing to uncertainties in how quasars populate dark matter halos (Shen et al 2009;White et al 2012;Conroy & White 2013;Cen & Safarzadeh 2015). Following the "Soltan" argument (Soltan 1982), which states that the luminosity function of quasars as a function of redshift reflects the gas accretion history of local remnant black holes, Yu & Tremaine (2002) estimated the mean lifetime of luminous quasars from local early-type galaxies to be t Q ∼10 7 -10 8 yr. Further constraints on quasar activity on timescales between ∼10 5 and 10 7 yr have been set by measuring an ionization "echo" of the quasar, which denotes the time lag between changes in the quasar's ionization rate and the corresponding changes in the opacity of the surrounding intergalactic medium (IGM; Adelberger 2004;Hennawi et al 2006;Schmidt et al 2017;Bosman et al 2020). A recent compilation of studies on the timescales governing the growth of SMBHs can be found in Inayoshi et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the preferred bubble size here (∼ 3 -15 cMpc) is still comparable to that predicted in Yajima et al (2018) where they calculate the size of H II regions created by LAEs at z ∼ 8 through semi-analytic modeling: ∼ 2 -9 cMpc from M star = 10 8−10 M galaxies (see their Figure 10). Additionally, it is worth discussing the chance of detecting double-peaked Lyα emission from our LAEs as the recent discoveries of double-peaked Lyα emission at z 6 (Hu et al 2016;Matthee et al 2018;Songaila et al 2018;Bosman et al 2020) suggest that LAEs which reside in a highly-ionized region could present double-peaked Lyα emission. Specifically, the preferred ionized bubble size from our calculation seems larger than the estimated bubble size of COLA1, a double-peaked LAE at z = 6.593, which could form its ∼2.3 cMpc ionized bubble (Matthee et al 2018).…”
Section: H I Fraction In the Igm At Z ∼ 76mentioning
confidence: 99%
“…Recent studies have been tackling this problem by counting galaxies in the quasar fields (see e.g., García-Vergara et al 2021;Simpson et al 2014;Habouzit et al 2019;Ota et al 2018;Bañados et al 2013;Kim et al 2009;McGreer et al 2014, and the references therein). However, because galaxies are biased tracers of the density field and may be impacted by the radiation feedback from the quasar (Kitayama et al 2000;Kashikawa et al 2007;Chen 2020;Bosman et al 2020), it is hard to estimate the real underlying density field using a few detected galaxies. Also, because the selection is done based on only a few wavebands, there could be interlopers in the foreground, and the completeness of these sources is also hard to quantify.…”
Section: Introductionmentioning
confidence: 99%